Human face recognition methods based on principle component analysis (PCA), wavelet and support vector machine (SVM) : a comparative study - Eman A. Gheni; Zahraa M. Algelal (Institute of Advanced Engineering and Science, 2020)
Human face Recognition systems are increasingly gaining more importance and can be utilized throughout many applications like video surveillance, Security, human-computer intelligent interaction, etc. this paper presents performance comparison between three feature extraction techniques for an automatic face recognition system. In the first step, we benefit from wavelet Transforms, principal component analysis (PCA) and combining Wavelet with PCA as feature extracting methods. After feature vectors generation, linear and nonlinear support vector machines (SVM) are usually used for implementing the classification or recognition step. These methods are compared on accuracy in an ORL database for face recognition applications including 400 images of 40 people.